A comunicação publicitária como reencantamento: a relação entre publicidade e religião no Brasil e na América Latina - Silva, Deborah Pereira da (2008)
In the research all these intellectual construction is configured in a specific loci, Brazil and Latin America, which gives the character of relevancy through the different approach. Extensive region in Weir sacred and profane are profoundly crossed since colonial times elaborating and reelaborating different ways to reenchant life. This work has as objective to study the relationships that take place between advertisement and religion in the sense of showing how the first one can take the place of the second one in the function of reenchantment of the life. The theory that supports this objective is that the concept of enchantment suffered alterations along the time, the first moment of transformation is the one that points out that religion would have lost its function of enchanting life, by the impacts brought from the advancements of science and technology, comprised in economical development. In the first part one worked with Max Weber, as it is from his creation the disenchantment of the world concept. From there we looked to follow the path to understand how and why religion dislocated itself as center of life meaning and allowed economy, through puritan ethics, science and technology, to slide the meaning of life to advertisement and consumption. This repositioning indicates an enormous emptiness of meanings. To work with the concept of emptiness, some Freud s ideas were used to understand the human tendency of not accepting a world without enchantment. In the sequence of this work, it was investigated how the concept of enchantment left religion and anchored itself in advertisement and, bringing two authors to the debate Angus and Jhally , because both discuss the possibility of this crisscrossing. Because advertisement is the spokesman of consumption society, Canclini was brought to illuminate consumption, in Latin America, specially, and also Marx, with two of his fundamental concepts of fetish and reification. Lotman is fundamental to study the relationships with culture semiotics, and Morin, to help understand distinct and complex aspects of different cultures. In this research approximations and distancing are discussed have elaborated the main theme in the Latin America region, mainly because of cultural hybridization in comparison to the other regions of the world where the disenchantment brought by science and technology is more significant